Bractwa szkaplerzne – duchowe wspólnoty wiernych - Warda, Elwira (Archiwa, Biblioteki i Muzea Kościelne, 2021)
Scapular brotherhoods are religious associations, whose members are obliged to wear a “small” scapular of a specific style and colour, expressing the relationship with the spirituality of the religious order, with which the brotherhood is linked. The origins of scapular brotherhoods date back to the 13th century, and the first ones were established in Florence, Bologna, Venice and other Italian towns. Scapular brotherhoods include: the Brotherhood of the Holy Trinity, the Brotherhood of Our Lady of Mount Carmel, the Brotherhood of Our Lady of Sorrows, the Brotherhood of the Immaculate Conception, the Brotherhood of Our Lady of Good Counsel, the Brotherhood of St. Cross and Bitter Passion of the Lord Jesus, the Brotherhood of Our Lady of Health of the Sick, the Brotherhood of Our Lady of Charity, the Brotherhood of the Precious Blood of Our Lord Jesus Christ, the Brotherhood of St. Benedict and the Brotherhood of St. Michael the Archangel.